Cosmopolitanism, Assignment Duration, and Expatriate Adjustment: The Trade-Off between Well-Being and Performance - Amir Grinstein; Luc Wathieu (European School of Management and Technology (ESMT), 2008)
This paper questions the notion that expatriates should adjust to their host country, by showing that adjustment and its consequences are affected by cosmopolitanism and expected assignment duration. A study of 260 expatriates in the U.S. reveals that cosmopolitans expecting shorter (longer) assignments adjust more (less) to both work and non-work aspects of their host country, and that this is associated with increased well-being. In contrast, for non-cosmopolitans, more well-being occurs when longer (shorter) expected assignments are accompanied by increased (decreased) work and non-work adjustment. Further, from the findings emerges a clash between two aspects of successful expatriation - well-being and professional success: while non-work adjustment is not always associated with well-being, work adjustment is positively related to assignment performance across conditions and subjects.
urn:nbn:de:101:1-201106143550
Keywords: D23; 650; Expatriates; international assignment; cosmopolitanism; crossculture adjustment; multinational corporations; preference persistence; assignment duration; survey method